Inquiry-based literature instruction in the 6-12 classroom : a hands-on guide for deeper learning - Ruday, Sean; Caprino, Katie (Eye on Education book., 2021)
"This practical and engaging book will help you learn how to teach literature with an inquiry-based approach. Inquiry-based literature instruction is an effective method to facilitate student engagement, motivation, and understanding in middle and high school ELA classrooms. Easy-to-implement and adaptable for many types of texts, this method encourages students to make authentic connections between texts, their lives, and real-world issues. In this classroom-ready resource, Ruday and Caprino walk through this instructional approach to demonstrate how using essential questions and a variety of texts will engage students in thought-provoking inquiry and promote meaningful learning. This book features: Three inquiry-based units applicable for middle and high school ELA and English classrooms A range of models of what inquiry-based literature instruction looks like in practice A chapter on culturally responsive teaching and supporting ELLs Guides, templates, and resource lists to help you plan your own inquiry-based literature teaching Throughout the book Ruday and Caprino share a wealth of insights and resources to support you when for putting inquiry-based instruction into practice"- Resumé vydavatel